2019
DOI: 10.1002/smll.201902118
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CaO2 Nanocrystals and Their Spherical Aggregates with Uniform Sizes for Use as a Biodegradable Bacteriostatic Agent

Abstract: As a solid precursor to O2 and hydrogen peroxide (H2O2), calcium peroxide (CaO2) has found widespread use in applications related to disinfection and contaminant degradation. The lack of uniform nanoparticles, however, greatly limits the potential use of this material in other applications related to medicine. Here, a new route to the facile synthesis of CaO2 nanocrystals and their spherical aggregates with uniform, controllable sizes is reported. The synthesis involves the reaction between CaCl2 and H2O2 to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 29 publications
1
73
0
Order By: Relevance
“…CaO 2 hydrolyzes to generate H 2 O 2 and, subsequently, O 2 , when in contact with water, as shown in Equation (2) [ 12 ]. To determine the oxygen generation efficiency of TA/CaO 2 by hydrolysis, a fixed amount of each TA/CaO 2 sample was added to PBS (pH 7.4) and the amount of dissolved oxygen in the solution was measured ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CaO 2 hydrolyzes to generate H 2 O 2 and, subsequently, O 2 , when in contact with water, as shown in Equation (2) [ 12 ]. To determine the oxygen generation efficiency of TA/CaO 2 by hydrolysis, a fixed amount of each TA/CaO 2 sample was added to PBS (pH 7.4) and the amount of dissolved oxygen in the solution was measured ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the resultant products are non-uniform in size. To address these drawbacks, Shen et al reported an alternative method for the preparation of CaO 2 nanoparticles using polyvinyl pyrrolidine as a colloidal stabilizer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above theory, Xia et al reported an approach to synthesize CaO 2 nanocrystals and their spherical aggregates [ 41 ]. They chose ethanol as the solvent to reduce the hydrolysis of CaO 2 NPs.…”
Section: Synthesis and Surface Modification Of Momentioning
confidence: 99%
“…However, the widespread misuse of antibiotics in healthcare and agriculture causes noticeable resistance due to spontaneous bacterial mutation and horizontal gene transfer. [1][2][3] Although massive efforts have been done to counteract this resistance, such as unnecessary medication reduction, antibiotic combinations, and new antibiotics discoveries, [4][5][6][7] it is still challenging to completely avoid the emergence and spread of the resistance due to the strong adaptability of the bacteria. To prevent the resistance from evolving, there is an urgent need to develop unconventional strategies to control antibiotic functions and realize on-demand bacterial inhibition.…”
Section: Introductionmentioning
confidence: 99%